2020
DOI: 10.1186/s12958-020-00682-0
|View full text |Cite
|
Sign up to set email alerts
|

Tripeptidyl peptidase I promotes human endometrial epithelial cell adhesive capacity implying a role in receptivity

Abstract: The endometrium undergoes cyclic remodelling throughout the menstrual cycle in preparation for embryo implantation which occurs in a short window during the mid-secretory phase. It is during this short ‘receptive window’ that the endometrial luminal epithelium acquires adhesive capacity permitting blastocysts firm adhesion to the endometrium to establish pregnancy. Dysregulation in any of these steps can compromise embryo implantation resulting in implantation failure and infertility. Many factors contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We have previously shown that in human endometrial epithelial cells, knockdown of TPP1 impairs cell adhesion by targeting BCL2 and P53 [ 10 ]. Although TPP1 knockdown similarly affected cell adhesion in the HTR8/SVneo cells, no significant changes were recorded on the expression of BCL2 and P53, suggesting cell type-specific regulation of targeted genes to control cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that in human endometrial epithelial cells, knockdown of TPP1 impairs cell adhesion by targeting BCL2 and P53 [ 10 ]. Although TPP1 knockdown similarly affected cell adhesion in the HTR8/SVneo cells, no significant changes were recorded on the expression of BCL2 and P53, suggesting cell type-specific regulation of targeted genes to control cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Although TPP1 knockdown similarly affected cell adhesion in the HTR8/SVneo cells, no significant changes were recorded on the expression of BCL2 and P53, suggesting cell type-specific regulation of targeted genes to control cell adhesion. We have also reported that TPP1 knockdown in primary human endometrial stromal cells does not impact decidualization or expression of decidualization markers [ 10 ]. In this study, TPP1 was detected at appreciable levels in the decidual cells across all trimesters of pregnancy, with a lower level which has been observed in the second trimester.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations